Defending the Swedish Model: Social Democrats, Trade Unions, and Labor Migration Policy Reform - Bucken-Knapp, Gregg (Lexington Books, 2009)
Across Europe, the prospect of a rapidly shrinking workforce has put increased labor migration back on the political agenda. However, for many on the left, concerns exist that less restrictive labor migration policies threaten core features of the social democratic project. This is perhaps clearest in Sweden, which in late 2008 adopted a liberal approach to third-country national labor migration, allowing employers to hire freely from outside the European Union. Defending the Swedish Model explores the debate leading up to this reform, focusing on the preferences of the Swedish Social Democratic Party (SAP) and the Swedish Trade Union Confederation (LO). While generally positive to the economic potential of increased labor migration, these allies remained highly skeptical towards calls from employers and bourgeois parties for liberalization. Bucken-Knapp argues that the SAP and LO develop their labor migration policy preferences on the basis of whether specific reform alternatives are perceived as being consistent with, or as undermining, the Swedish model. In the case of third-country nationals, both allies considered liberalization a threat to full employment aims, instead seeking to preserve an influential role for the state labor market board and organized labor. Bucken-Knapp also focuses on the Swedish labor migration debate prior to the 2004 enlargement of the European Union, showing how SAP concerns over potential abuse of the universal welfare state led to its support for transitional arrangements. Defending the Swedish Model illuminates the challenges faced by social democrats and trade unions when considering the need for increased labor migration.